A COMPREHENSIVE REVIEW OF RECENT ADVANCEMENTS IN VIGNA RADIATA RESEARCH: INSIGHTS INTO PHYSIOLOGY, AGRONOMIC, NUTRITIONAL, AND HEALTH PERSPECTIVES - Acharjee, Swagato; Sengupta, Sudeshna; Bhattacharya, Malavika (International Journal of Research -GRANTHAALAYAH, 2024)
Aims: The primary aim of this research is to provide a better comparative understanding of the Physiology, Agronomic, Nutritional, and Health-modulating effects observed in the reviewed studies related to Vigna radiata consumption. The review paper typically highlights the antidiabetic, anticancer, anti-inflammatory, and immunomodulatory effects of Vigna radiata (mung bean). The fact that there exist inconsistencies and gaps in evidence against certain effects of mung bean & places where further research is needed is also addressed in the review paper Place and Duration of Study: Department of Biotechnology, Techno India University, West Bengal, India; between August 2023 and July 2024. Methodology: The paper has been prepared by conducting a comprehensive search of various mung bean-related scientific literature databases across the internet mung beans, followed by extracting relevant data from selected studies, evaluating quality assessment factors & finally summarizing and synthesizing the extracted data, including the main findings related to Vigna radiata's beneficial effects. Results: The review work seems to be beneficial for reaffirming the significance of Vigna radiata as a natural source of immunity support and summarizing the key takeaways from the review. Conclusion: The mung bean (Vigna radiata) is a leguminous fodder crop which is rich in nutrients and bioactive compounds, including polyphenols, polysaccharides, and polypeptides. Studies conducted in vitro and in vivo highlight the variety of mung bean's health benefits. It portrays antidiabetic, anticancer, anti-inflammatory, and immunomodulatory effects. However, it is imperative to delve deeper into the mechanisms underlying their role in preventing diseases. There are substantial knowledge gaps regarding the bioactive compounds and biological functions of mung beans. Further investigation is crucial to pinpoint additional essential components responsible for their health advantages and underscore these various components' combined effects on biological processes.